2020
DOI: 10.1038/s41523-020-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of breast papillary lesions as a predictor of progression to carcinoma

Abstract: Intraductal papillomas (IDP) are challenging breast findings because of their variable risk of progression to malignancy. The molecular events driving IDP development and genomic features of malignant progression are poorly understood. In this study, genome-wide CNA and/or targeted mutation analysis was performed on 44 cases of IDP, of which 20 cases had coexisting ductal carcinoma in situ (DCIS), papillary DCIS or invasive ductal carcinoma (IDC). CNA were rare in pure IDP, but 69% carried an activating PIK3CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…SF3B1 c.2098A>G) or ADH ( GATA3 c.925-3_925-2del). This is consistent with previous reports and reports of field effect mutations in normal ducts or benign lesions [32,33], though the contribution of these mutations to the lesion progression remains to be determined.…”
Section: Resultssupporting
confidence: 93%
“…SF3B1 c.2098A>G) or ADH ( GATA3 c.925-3_925-2del). This is consistent with previous reports and reports of field effect mutations in normal ducts or benign lesions [32,33], though the contribution of these mutations to the lesion progression remains to be determined.…”
Section: Resultssupporting
confidence: 93%
“…Kader et al recently published data suggesting that IDP with no copies number alterations (CNA), independently of the histological subtype, clinical data or age of the patient, lack malignant progression potential. This evidence arises the possibility to avoid surgical excision in these patients [78]. It has also been demonstrated IDP may progress directly into DCIS and IDC of any grade, showing that these different entities can share molecular genetic features and have a common etiology [79].…”
Section: Future Perspectivementioning
confidence: 94%
“…This information suggests that the absence of CNA (16q loss, 1q gain, 11q loss) and the presence of PIK3CA mutation in IDPs may be a biomarker of low risk for malignant transformation, regardless of pathologic features (benign or atypical IDP) and clinical findings. Further studies are needed to confirm these data [78]. With molecular biomarkers advances, a genome-wide CNA and/or targeted mutation analysis should be considered as the presence/absence of CNA (16q loss, 1q gain, 11q loss) and PIK3CA mutation may serve as potential biomarkers for predicting malignant progression/transformation.…”
Section: Future Perspectivementioning
confidence: 99%
“…Earlier molecular studies suggested that alterations of c-Met, RET/PTC, α3β1 integrin, Sonic hedgehog (Shh), and Bone Morphogenetic Protein (BMP) play a role in the development of papillary breast lesions [71]. Recently, progression to DCIS and invasive carcinoma was hypothesized for a subset of intraductal papilloma [40]. Intraductal papillomas were clonally related to synchronous DCIS and invasive carcinoma in more than 50%, even without papillary histology of the latter.…”
Section: Intraductal Papilloma With Adh Dcis or Lobular Neoplasiamentioning
confidence: 99%